Sorting the fishes caught according to their species and value - Mumbai Archive Project Team (Jio Institute, 2024)
The sorted and iced fish are taken to auction halls at the landing centers. Auctions usually take place early in the morning, facilitated by licensed auctioneers or agents who ensure fair prices and efficient sales. The primary bidders include wholesalers, fish vendors, and representatives from fish processing companies and export houses.